2020
DOI: 10.1016/j.jaim.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Allium cepa exerts neuroprotective effect on retinal ganglion cells of pterygopalatine artery (PPA) ligated mice

Abstract: Background Repeated failure to rescue the damaged retinal ganglion cells (RGCs) by various drugs has warranted the need to screen common herbal compounds available in the form of various eye formulations for their efficacy. Objective We aimed to investigate the neuroprotective effect of pretreatment with aqueous extract of A . cepa in Ischemia/Reperfusion (I/R) induced retinal injury. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The current study assessed the ability of topical onion juice to ameliorate age-related corneal changes based on histopathological, immunohistochemical and histomorphometric examinations. Despite their limited number, previous experimental studies assessed the effects of onion extracts on corneal changes related to different animal models [18,28], in addition to the effects of onion extracts on the pathological changes of other ocular structures [19,29,30]. Furthermore, several publications indicated that age has major changes on the cornea [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The current study assessed the ability of topical onion juice to ameliorate age-related corneal changes based on histopathological, immunohistochemical and histomorphometric examinations. Despite their limited number, previous experimental studies assessed the effects of onion extracts on corneal changes related to different animal models [18,28], in addition to the effects of onion extracts on the pathological changes of other ocular structures [19,29,30]. Furthermore, several publications indicated that age has major changes on the cornea [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It's a 2 hr occlusion model followed by reperfusion for 3 different time points: 7, 21, and 28-day. Because of the repeated failure (24) and side effects (25) of the available commercial drugs, we wanted to test the alternative approach of testing A. cepa (onion) as the pretreatment strategy to explore if it is able to improve the vision or not. Apart from its many biological benefits in the form of antioxidant, anti-inflammatory, and neuroprotective activity (as shown by previous studies) its common availability makes it an important biological product to be tested for its efficacy (5,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…The complete experiment was carried according to the GLP guidelines at Neuroscience Research Laboratory (19,20). The A. cepa extract preparation is detailed in our previous publication (21). Different dosages of A. cepa (100 mg/kg, 200 mg/kg, 300 mg/kg) was administered 24 hours prior to the surgery.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Additionally, whether the bench work has been carried out according to the Good Laboratory Practice (GLP) guidelines or not can also be assessed. 6 At the institution level, there are various rules and guidelines for responsible conduct of research. 7 This includes ethical orientation and guidance for researcher, instituting plagiarism check before submission, availability of data in the repository system, supervision of research being conducted, data ownership, data retention, and long-term storage in the form of e-copy besides early reporting of any such misconduct, etc.…”
mentioning
confidence: 99%
“…Additionally, whether the bench work has been carried out according to the Good Laboratory Practice (GLP) guidelines or not can also be assessed. 6 …”
mentioning
confidence: 99%